Fiscal Decentralization or Centralization: Diverging Paths of Chinese Cities. Issue 3 (20th May 2019) - Yang, Shiming
Abstract: If fiscal decentralization promotes growth, why do some regions decentralize more than others? This article identifies the growing divergence of fiscal centralization among Chinese cities and explains it in a public finance framework. It argues that fiscal decentralization and its economy‐liberalizing effect entail significant short‐term fiscal risk. The more a locality relies on uncompetitive business ownership for fiscal revenue, the less likely fiscal decentralization is to occur. This article compiles a dataset of 20 provincial capitals between 1999 and 2016 to test for the connection between a city's tax base and its fiscal centralization level. It then pairs two "most similar" cities to trace how fiscal security concerns drove their fiscal and economic policies apart. This article adds a micro‐level perspective to the literature on fiscal federalism. By pointing out the fiscal constraints confronting local governments, it offers a new angle to understand the different growth paths of Chinese cities.